Process evaluation of the Sophia Step Study- a primary care based three-armed randomized controlled trial using self-monitoring of steps with and without counseling in prediabetes and type 2 diabetes - Jenny Rossen; Maria Hagströmer; Agneta Yngve; Kerstin Brismar; Barbara Ainsworth; Unn-Britt Johansson (BMC, 2021)
Abstract Background Describing implementation features of an intervention is required to compare interventions and to inform policy and best practice. The aim of this study was to conduct a process evaluation of the first 12 months of the Sophia Step Study: a primary care based RCT evaluating a multicomponent (self-monitoring of daily steps plus counseling) and a single component (self-monitoring of steps only) physical activity intervention to standard care on cardiometabolic health. Methods The evaluation was guided by the Medical Research Council Guidance for complex interventions. To describe the implementation communication with the health professionals implementing the interventions, attendance records and tracking of days with self-monitored pedometer-determined steps were used. Change in physical activity behaviour was measured at baseline, 6 and 12 months as daily steps by accelerometry. Results During April 2013 to January 2018 188 participants were randomized and intervened directly after inclusion. Response rate was 49% and drop out was 10%. A majority, 78%, had type 2 diabetes and 22% were diagnosed with prediabetes. Mean [Standard deviation (SD)] body mass index was 30.4 (4.4) kg/m2 and steps per day was 6566 (3086). The interventions were delivered as intended with minor deviation from the protocol and dose received was satisfying for both the multicomponent and single component group. The mean [95% Confidence Interval (CI)] change in daily steps from baseline to 6 months was 941(227, 1655) steps/day for the multicomponent intervention group, 990 (145, 1836) step/day for the single component group and − 506 (− 1118, 107) for the control group. The mean (95% CI) change in daily steps from baseline to 12 months was 31(− 507, 570) steps/day for the multicomponent intervention group, 144 (− 566, 853) step/day for the single component group and − 890 (− 1485, − 294) for the control group. There was a large individual variation in daily steps at baseline as well as in step change in all three groups. Conclusions Applying self-monitoring of steps is a feasible method to implement as support for physical activity in the primary care setting both with and without counseling support. Trial registration ClinicalTrials.gov , NCT02374788 . Registered 2 March 2015.